A highly emissive Zn(ii)-pyridyl-benzimidazolyl-phenolato-based chemosensor: detection of H2PO4−via "use" and "throw" device fabrication. Issue 44 (2nd November 2021) - Dey, Sunanda; Paul, Sukanya; Debsharma, Kingshuk; Sinha, Chittaranjan
Abstract : A highly emissive Zn(ii )-pyridyl-benzimidazolyl-phenolato-based chemosensor is used in the solution-state and cost-effective 'on-site' solid-state contact mode detection of H2 PO4 − . Abstract : 2-Ethoxy-6-[1-(phenyl-pyridin-2-yl-methyl)-1 H -benzoimidazol-2-yl]-phenol (HL) selectively serves as a sensitive 'turn on' Zn 2+ sensor in 9 : 1 (v/v) DMSO/H2 O (HEPES buffer, pH = 7.4) medium in the presence of sixteen other cations at the limit of detection (LOD) of 3.2 nM. The strong blue emission of the complex, [Zn(L 1 )OAc] (HL 1 = benzimidazolyl ring-opening structure of HL) ( λ em, 461 nm), is quenched by H2 PO4 − in the presence of eighteen other anions and the LOD is 0.238 μM. The emission of the complex is due to restricted intramolecular rotation (RIR) followed by chelation-enhanced fluorescence (CHEF). The quenching of the emission of [Zn(L 1 )OAc] by H2 PO4 − (in the presence of other P V s (inorganic and biological) as well as additional anions) is due to the 'turn off' fluorescence via the demetallation and release of the nonfluorescent ligand, HL, and [Zn(H2 PO4 )] + . An INHIBIT logic gate memory circuit of the probe HL was devised with Zn 2+ and H2 PO4 − as two consecutive inputs. The percentage of H2 PO4 − recovery was excellent and was obtained from distilled, tap, and drinking water sources. The bright blue emission of [Zn(L 1 )OAc] further triggered the fabrication of ready-made portable thin films of the Zn-complex, which executed a cost-effective 'on-site' solid-state contact mode detection of H2 PO4 − with selectivity at the picogram level (10.97 pg cm −2 ) by monitoring the intensities of quenched spots under UV light upon varying the analyte concentration from 10 −8 to 10 −3 M. Finally, taking advantage of reversible fluorescence switching, a simple and definite ion-responsive security feature was successfully embedded into a "use" and "throw" solution-coated paper strip of the Zn(ii )-pyridyl-benzimidazolyl-phenolato-based chemosensor, which efficiently detected H2 PO4 − in water by a successive 'ON–OFF' fluorescence switching-driven security activity without any exhaustion of the emission phenomenon.